Dansk kunst i DDR: En samlingshistorie på tværs af Jerntæppet - Handberg, Kristian (Periskop – Forum for kunsthistorisk debat, 2025)
Kunsthalle Rostock (opened 1969) was an important exhibition venue in the former German Democratic Republic. It was the only newly built art museum in the GDR and was the setting for the Biennale der Ostseeländer, where art from the Nordic countries and the state socialist countries on the Baltic Sea was exhibited in the first named “Biennale” in the Nordics from 1965. In parallel with several exhibitions by Danish artists, works by Danish and Nordic artists were also acquired. This created a collection of hundreds of works of Danish art, primarily in a realist style and often by artists from the associations Corner and Kammeraterne. Sometimes the Kunsthalle Rostock was even referred to as a museum of Nordic art and director from 1965 to 1985, Horst Zimmermann prioritized this collection and also established contacts with a number of Danish artists such as Victor Brockdorff and Jørgen Buch. This collection is relatively unknown in Danish art history and also in the German context after the reunification in 1990. The article explores for the first time the Danish collection in Rostock, the institutional framework, the artistic composition and the political significance of the initiative and other examples of Danish art exhibited in the GDR.